Association of bisphenol A, bisphenol F, and bisphenol S with ADHD symptoms in children. (March 2022) - Kim, Johanna Inhyang; Lee, Young Ah; Shin, Choong Ho; Hong, Yun-Chul; Kim, Bung-Nyun; Lim, Youn-Hee
Graphical abstract: Highlights: Bisphenol F (BPF) and S (BPS) have been suggested to have neurotoxic effects. We examined exposure to bisphenols and attention-deficit hyperactivity symptoms (ADHD). The detection frequency of BPF and BPS increased greatly from age 6 to age 8. Exposure to BPF and BPS were associated with greater ADHD symptoms at age 6. Bisphenol A (BPA) showed nonlinear relationships with ADHD symptoms. The association of BPA and ADHD was pronounced above a threshold of 3.0 μg/g creatinine. Abstract: Background: Bisphenol A (BPA) has been linked to attention-deficit/hyperactivity disorder (ADHD) symptoms, but the neurotoxic effects of bisphenol substitutes such as bisphenol F (BPF) and S (BPS) have not been well investigated. We investigated the associations between BPA, BPF, and BPS with ADHD symptoms at multiple time points in children. Methods: The levels of BPA (at ages 4, 6, and 8), BPF (at ages 6 and 8), and BPS (at ages 6 and 8) were measured in 619 children. Because of the low detection frequency of BPF and BPS levels, participants were divided into categories (<or ≥ limit of detection (LOD) for BPF; < LOD, ≥ LOD and < median, or ≥ median for BPS). ADHD symptoms were assessed using the ADHD Rating Scale IV (ARS). The relationship between bisphenols and ARS scores was analyzed using Poisson regression models, and generalized additive models and piecewise regression models were further explored for BPA. Results: BPA was detected in most participants (>97%), whereas BPF and BPS were less frequently detected (age 6: 17.5% for BPF and 42.0% for BPS; age 8: 51.6% for BPF and 73.3% for BPS). Doubling in BPA levels was associated with increased ARS scores by 4.7% (95% confidence intervals [CI]: 0.5, 9.2) at age 6. The association was greater with BPA levels higher than 3.0 μg/g creatinine (24.2% [95% CI: 15.5, 33.6] increase). The BPF ≥ LOD group had 10.8% (95% CI: 1.2, 21.4) higher ARS scores than the BPF < LOD group. The BPS ≥ median group had 11.4% (95% CI: 2.0, 21.7) higher ARS scores than the BPS < LOD group. Conclusion: All bisphenols, in particular those at or above the LOD or median levels, were associated with ADHD symptoms at age 6. Further prospective studies are warranted to determine causal inference.